PREPARATION AND CHARACTERIZATION OF YBA2CU3O7-X POWDER BY THE ULTRASONIC SPRAY PYROLYSIS METHOD - KIM, IT; OH, TS; KIM, YH (CHAPMAN HALL LTD, 1991)
A single-phase YBa2Cu3O7-x, powder was prepared in an air flow system by thermally decomposing droplets containing the nitrate salts of yttrium, barium and copper in distilled water. The powder obtained had a mean particle size 0.78-mu-m and a very narrow particle size distribution. The total porosity of the powder was estimated to be about 63%. It was found that much agglomeration had occurred among the droplets, which would have an adverse effect on the particle size distribution. The bulk density of a sintered specimen using the powder prepared at 950-degrees-C was higher than 97% theoretical density.
Keywords: FINE PARTICLES; METAL ALKOXIDE; SUPERCONDUCTORS